KLASIFIKASI RESPON SISWA DALAM MENYELESAIKAN SOAL CERITA POLA BILANGAN BERDASARKAN TAKSONOMI SOLO - Carolina Chrisna Hirera; Edy Yusmin; Romal Ijuddin (UNIVERSITAS TANJUNGPURA, 2023)
This study aimed to (1) determine the classification of students’ response in completing story questions based on the SOLO taxonomy; (2) discover the challenges of students in completing story questions on number patterns. The methodology used in this study was descriptive qualitative with a case study approach. The participants were 22 of 8th-grade students at SMP Sugiyopranoto Sanggau and the data sources were the results of story questions on number patterns and interview transcripts with the students. The result of this study indicates that response of high-achiever students reach the relational level of 8%, the students have already understand the number pattern materials quite well, take notes all the information contained on the questions, are able to correlate the separate information properly, write down the calculation steps and the conclusions given were also relevant. The response of moderate-achiever students reach the multistructural level of 40%, the students sufficiently understand the questions, take notes several important information and utilize it at the calculation, however, the correlation of separate information and concepts were not clear so that the calculation and the answers obtained were not reasonably right. Meanwhile, the response of low-achiever students are at the unistructural level of 21%, the students were still formula-oriented, and used merely one concept or one calculation step which caused the results obtained to be incorrect.